Aerosol generation from graphite at high temperature: Role of heating rate and air flow rate - Yadav S.K.; Joshi M.; Shukla P.; Khan A. (My University, 2025)
Behavior of graphite at high temperature in terms of emission characteristics of aerosols has received notable importance in the recent past. Information on the physico-chemical characteristics of generated particles during air ingress conditions for high temperature reactors (HTRs) is crucial for design and safety considerations. The present study focuses on studying the effects of varying heating rate and air flow rate on the number concentration characteristics of particles and gases (CO and CO2) generated from heated graphite. Overall, the peak of evolution profile of number concentration of particles and volume concentration of CO gas was observed in between 600 and 800 °C. With an increase in heating rate, higher particle number concentration and shifting of peak towards high temperatures was noted. Although this trend remained more or less similar, number concentration reduced with the increase in air flow rate. Experimental observations have also been supplemented with plausible mechanism in this work. © 2021 Elsevier Ltd